PENGARUH KEPEMIMPINAN, KOMITMEN ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PADASA ENAM UTAMA KECAMATAN KAMPAR HULU KABUPATEN KAMPAR - Melisa Melisa; Dewita Suryati Ningsih; Taufiqurrahman Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the PT. Padasa Enam Utama kececamatan Kampar Hulu, Kabupateb Kampar with the aim to analyze the influence of leadership, organizational commitment and discipline for work performance of employees in the PT. Padasa Enam Utama Kecamatan Kampar Hulu, Kabupaten Kampar. The population in this study is numbered 48 employees with census method then obtained the number of samples is equal to the population of 48 people. The collection techniques of data was done through the technique of questionnaires, interviews, while the data form the primary data and secondary data, then the data were analyzed using multiple linear regression data analysis. The Coefficients of determination, correlation coefficients, simultaneous test and partial test. In this study, there are four variables: Performance (Y) as the dependent variable, Leadership (X1), organizational commitment (X2), and Discipline work (X3). This research was conducted by giving questionnaires to employees of the PT. Padasa Enam Utama Kecamatan Kampar Hulu, Kabupaten Kampar. The results showed that the variables of leadership, organizational commitment and discipline simultaneously significant effect on employee performance. This is evident from the results of test of F hitung > F table. Furthermore, based on t test results partially known that the result of the t test for variable leadership was significantly on employee performance on which t hitung > table, the t test for variable organizational commitment significantly on employee performance which t thitung > t table, and the t test for variable work discipline also significant affect on employees performancethitung>tabel.Keywords : Leadership, Organizational Commitment, Discipline Work, And employee Performance